Superwetting membrane with double-layer and hierarchical structure constructed from poly-caffeic acid (PCA) coating and various CA-metal ions/nanoparticles networks. (December 2022) - Zhang, Yuxin; Wang, Yong; Wang, Duo; Zhang, Zhiyu; Qi, Tao; Guo, Qingchun
Abstract: Superwettability modification of membrane surface has attracted extensive attention for efficient oil/water emulsion separation in view of membrane antifouling. The design of micro- and nanoscale structure on membrane surface, which plays an important role in improving wettability is significant but remains challenging. In this study, inspired by polyphenols coating and multifunctional metal-phenolic networks (MPNs), a series of superwettable membranes with double-layer and hierarchical structure derived from PCA coating and various CA-metal ions (nanoparticles) networks were facilely obtained. Specifically, the PCA former layer provided hydrophilic basis, and the CA-metal ions (nanoparticles) networks provided hierarchical micro- and nanoscale structures. The obtained membranes with double layer and hierarchical structures were thus bestowed superhydrophilic, underwater superoleophobic and antifouling features, which made it capable of efficient oil/water emulsion separation with high oil rejection (all higher than 98.8 %). In addition, the obtained membranes possessed satisfactory self-clean ability, stability, and mechanical property. The demonstrated PCA/CA-metal ion (nanoparticles) derived strategy for double-layer and hierarchical structures modification in this work may offer a pave way to endow various materials with superwettability and antifouling property for multiple applications. Graphical abstract: Unlabelled Image Highlights: Caffeic acid/metal ions (nanoparticles) networks were applied to surface modification for enhancing superwetting ablity Polyphenols coating and Metal-phenolic networks (MPNs) derived double-layer was constructed on membrane surface The membranes exhibited exceptional performance in oil/water emulsion separation The membranes showed appreciable self-cleaning ability, mechanical property and stability